2015
DOI: 10.1007/978-3-319-16199-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Expansion of a Food Image Dataset Leveraging Existing Categories with Domain Adaptation

Abstract: In this paper, we propose a novel effective framework to expand an existing image dataset automatically leveraging existing categories and crowdsourcing. Especially, in this paper, we focus on expansion on food image data set. The number of food categories is uncountable, since foods are different from a place to a place. If we have a Japanese food dataset, it does not help build a French food recognition system directly. That is why food data sets for different food cultures have been built independently so f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(122 citation statements)
references
References 18 publications
0
122
0
Order By: Relevance
“…They used the pre-trained AlexNet model as a feature extractor and integrated both CNN features and Fisher Vector encoded conventional SIFT and color features. Yanai et al [21] fine-tuned the AlexNet model and achieved the best results on public food datasets so far, with top-1 accuracy of 78.8% for UEC-FOOD-100 dataset and 67.6% for UEC-FOOD-256 [22] (another Japanese food image dataset with 256 classes). Their works showed that the recognition performance on small image datasets like UEC-FOOD-256 and UEC-FOOD-100 (both of which contained 100 images for each class) can be boosted by fine-tuning the CNN network which was pre-trained on a large dataset of similar objects.…”
Section: Food Image Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…They used the pre-trained AlexNet model as a feature extractor and integrated both CNN features and Fisher Vector encoded conventional SIFT and color features. Yanai et al [21] fine-tuned the AlexNet model and achieved the best results on public food datasets so far, with top-1 accuracy of 78.8% for UEC-FOOD-100 dataset and 67.6% for UEC-FOOD-256 [22] (another Japanese food image dataset with 256 classes). Their works showed that the recognition performance on small image datasets like UEC-FOOD-256 and UEC-FOOD-100 (both of which contained 100 images for each class) can be boosted by fine-tuning the CNN network which was pre-trained on a large dataset of similar objects.…”
Section: Food Image Recognitionmentioning
confidence: 99%
“…The food images were selected from already existing and publicly available food image datasets, including Food-101 [17], UEC-FOOD-100 [20] and UEC-FOOD-256 [22]. The food images were selected in such a way that they could cover a wide variety of food items.…”
Section: Dataset 1: Food-5kmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Branson et al 12) proposed complementary use of AMT with object classifiers by giving AMT workers simple easy questions to tackle difficult fine-grained object classification. Kawano et al 61) proposed to use AMT after applying automatic image re-ranking based on domain-adaptation which utilizes the knowledge of existing image categories for automatic extension of food image database. Note that not all the AMT workers are trusty, and some of them try to cheat requesters to save their time.…”
Section: )mentioning
confidence: 99%
“…The dataset contains 9, 060 images of 100 Japanese food categories. It has grown into UEC FOOD 256, which contains 31, 397 images of 256 categories [12]. One notable characteristic of these datasets is that bounding boxes indicating the location of foods in each image are also available.…”
Section: Related Workmentioning
confidence: 99%